Class system to develop the phrasal verbs vocabulary through warm-up as a methodological strategy - Delgado Mendoza, Yulissa Thalia; Agurto Jimenez, Ginger Lisbeth (Machala, Utmachala, 2023)
This research addresses problematic situations related to the English language teaching-learning process. Moreover, it aims at increasing language proficiency through motivational techniques at the beginning of a class. In this regard, it was proposed to elaborate a class system through a warm-up as a methodological strategy for developing phrasal verbs vocabulary in students from 9th of General Basic Education at the “Carmen Mora de Encalada” High School in the period of 2022. This project provides a positive-quantitate methodological paradigm by using a non-experimental design of the cross-sectional-descriptive type, which uses theoretical methods in order to explain and to characterize the study-object through a bibliographical information analysis. Furthermore, it uses empirical methods such as observation, pedagogical test and teacher interview to collect data in order to accept or reject the hypothesis. By the same token, after applying the class system there were significant changes in comparison to the previous students’ academic situation. Consequently, it is recommended to continue deepening into the aforementioned academic issue and finding and applying other ways to enhance the development of phrasal verbs vocabulary, due to the importance that they have within the mastery, use and management of the English language.
El presente trabajo de investigación atiende a situaciones problemáticas en torno al proceso de enseñanza-aprendizaje del inglés en el Ecuador y tiene como finalidad incrementar el dominio de la lengua meta a partir de técnicas motivadoras al inicio de la clase. Sobre esta base se plantea como objetivo elaborar un sistema de clases con el uso de warm-up como estrategia metodológica para desarrollar el vocabulario de phrasal verbs en alumnos de 9vo año de EGB paralelo “B” en el Colegio de Bachillerato “Carmen Mora de Encalada”. La investigación responde a un paradigma cuantitativo positivista, con un diseño no experimental de tipo transversal-descriptivo, el cual hace uso de métodos teóricos con el objetivo de explicar y caracterizar conceptualmente el objeto de estudio mediante un análisis de información bibliográfica. Así mismo, emplea métodos empíricos como la observación, prueba pedagógica y entrevista dirigida al docente para recolectar datos a fin de comprobar o rechazar la hipótesis. En este mismo contexto, a partir de la aplicación del sistema de clases se obtuvieron cambios significativos en comparación con el estado inicial en el que se desarrolló la investigación. Por lo que se recomienda continuar profundizando en la problemática que dio paso a esta investigación, tomando en cuenta otras vías de solución relacionadas al desarrollo de vocabulario de phrasal verbs debido a la importancia que poseen dentro del dominio, uso y manejo del idioma inglés.
Keywords: SISTEMA DE CLASE; WARM-UP; PHRASAL VERB; IDIOMA INGLES; VOCABULARIO